UKURAN KECAKAPAN PENYANDANG DISABILITAS TUNA AKSARA DALAM PERJANJIAN OTENTIK - Amin, Aidi; Zeinudin, Moh.; Fithry, Abshoril; Rofiqi, Imam (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
Authentic agreements are executed in the presence of a notary, what if the agreement is executed by a person with a disability who is illiterate, the provisions of Article 1320 of the civil law book contain requirements for agreement skills, in addition to the provisions of Article 9 of law number 8 of 2016 explaining that persons with disabilities have the right for equal treatment before the law. This research is normative by using a statutory approach, a conceptual approach, and an analytical approach. Persons with disabilities who are illiterate can carry out authentic agreements themselves in accordance with Article 9 of the disability law. If this is not possible, then: first, ask for help from a notary, second, give power of attorney to someone who is capable and third; ask for pardon from the district court for family assistance. As for legal remedies that can be implemented, namely by Negotiation and filing civil and criminal lawsuits. Keywords: Illiterate; Agreement; Authentic.